1995
DOI: 10.1021/tx00050a005
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Sp1 Zinc Finger 3 Peptide: Coordination Chemistry, Redox Reactions, and Metal Binding Competition with Metallothionein

Abstract: Toxic and/or carcinogenic consequences may result from metal ion substitution for the Zn-(II) in transcription factors containing zinc fingers, and the small Cys-rich metal-binding protein metallothionein (MT) may play a role in this metal substitution. To begin to evaluate this hypothesis, with regard to the carcinogenic metal ion Ni(II), a peptide corresponding to the third finger of the transcription factor Sp1 (Sp1-3) has been synthesized and its metal binding and redox reactions have been studied. The pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
73
3
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 58 publications
(95 reference statements)
10
73
3
1
Order By: Relevance
“…Another study indicated that MT is capable of restoring DNA binding of ER in metalhuman aMT has a higher affinity for nickel than zinc, possidepleted extracts. This effect is similar to that of addition of bly preventing nickel-induced toxicity [15]. In our study, we non-protein bound zinc in the form of zinc acetate.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Another study indicated that MT is capable of restoring DNA binding of ER in metalhuman aMT has a higher affinity for nickel than zinc, possidepleted extracts. This effect is similar to that of addition of bly preventing nickel-induced toxicity [15]. In our study, we non-protein bound zinc in the form of zinc acetate.…”
supporting
confidence: 80%
“…Nonetheless, the observed reversibility of zinc ex-~7 change in this study suggests that ER zinc fingers have an affinity for zinc similar to that of MT. While a recent study demonstrated metal exchange between a single synthetic Spl zinc finger peptide and the alpha domain of human MT [15], a contrasting report, [8] The reversible zinc exchange we report here indicates that lowing additions: (lanes) 1, no additions; 2, 0.7 mM zinc acetate;…”
contrasting
confidence: 59%
“…Then, Wilcox and coworkers [27] showed directly that a single Zn-finger from Sp1 reacted with the α-domain of metallothionein through a ligandsubstitution process. Similarly, Roesijadi and coworkers [28] recently observed that apoMT reacted with another C 2 H 2 Zn-finger peptide, Tramtrack, resulting in the inactivation of its capacity to bind to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, two reports have described chemical properties of the reaction of selected Znfinger peptides with apoMT or the α-domain of metallothionein [27,28]. The present experiments were undertaken to gain insight into the chemical properties of the reaction of Zn-TFIIIA with apoMT.…”
Section: Introductionmentioning
confidence: 98%
“…Buffer: 20 mM HEPES, pH 7, 25°C. a Abbreviations and references: Sp1 (F3), finger 3 of Sp1 transcription factor (Posewitz & Wilcox, 1995), CP1, consensus peptide derived from available sequences of N 2 S 2 domains (Krizek, Merkle & Berg, 1993).…”
mentioning
confidence: 99%